1992
DOI: 10.1021/ja00030a014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies toward a characterization of conceivable intermediates involved in the gas-phase oxidation of methane by bare FeO+. Generation of four distinguishable [Fe,C,H4,O]+ isomers

Abstract: Sections of the potential energy surface of [Fe,C,H4,0]+ ions are probed experimentally by using collisional activation mass spectrometry as well as theoretically by ab initio MO studies. Evidence is presented for the existence of several, clearly distinguishable isomers, some of which are of relevance in the context of methane activation by FeO+ in the gas phase. While this process initially gives rise to the formation of an encounter complex, CH4-FeO+ (1), both spontaneous and post-collisional isomerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
0
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 203 publications
(130 citation statements)
references
References 1 publication
10
114
0
5
Order By: Relevance
“…The structure of HOMgCH 3 is similar to that of HOFeCH 3 + in the dissociation of CH 4 on FeO + reaction. 23 From the atomic natural charges in Table 2, the electronic features support the view that HOMgCH 3 can be described as either CH 3 -interacting with MgOH + or OHinteracting with MgCH 3 + , since both the CH 3 and OH moieties are close to -1 valence and both MgOH and MgCH 3 moieties are close to +1 valence. These interactions are so large that the HOMgCH 3 molecule is especially stable.…”
Section: Interaction Between Mgo and Chmentioning
confidence: 54%
See 1 more Smart Citation
“…The structure of HOMgCH 3 is similar to that of HOFeCH 3 + in the dissociation of CH 4 on FeO + reaction. 23 From the atomic natural charges in Table 2, the electronic features support the view that HOMgCH 3 can be described as either CH 3 -interacting with MgOH + or OHinteracting with MgCH 3 + , since both the CH 3 and OH moieties are close to -1 valence and both MgOH and MgCH 3 moieties are close to +1 valence. These interactions are so large that the HOMgCH 3 molecule is especially stable.…”
Section: Interaction Between Mgo and Chmentioning
confidence: 54%
“…4 To obtain further information about this process, many theoretical studies of the interaction of methane with metal oxide heve been performed using an oxometal cluster model 9,16,[18][19][20][21] and gaseous metal oxide molecules. [22][23][24][25][26][27] Of particular interest is the direct oxidation of methane by metal oxide fragments, [22][23][24][25][26][27] because this process can be justifiably regarded as providing models for the more complicated processes of heterogeneous or enzymatic methane monooxygenase catalysis. It is obvious that a better understanding of the details of the activation processes would be desirable in order to improve the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…MoO 3 ϩ exhibits a KIE of the same magnitude, thus pointing to the operation of a similar mechanism (60). In the case of OFeOH ϩ (59) and FeO ϩ (52, 53), even larger KIEs are observed that, at least in the latter case, can be ascribed to the formation of an intermediate insertion species in conjunction with spin cross-over (81)(82)(83)(84)(85).…”
Section: Ligated Metal Cationsmentioning
confidence: 69%
“…Diese Erkenntnis ist nicht zuletzt Gasphasenstudien geschuldet, bei denen Metalloxide unterschiedlicher Stöchio-metrie unter wohldefinierten Bedingungen untersucht wurden; hierzu gehören [MgO]C + , [8] [FeO]C + , [9] [PbO]C + , [10] [ [19] In Anbetracht dieser drastischen Unterschiede schien es angebracht, Cluster mit systematisch variiertem Vanadium/PhosphorVerhältnis zu studieren. Das enorme Interesse an solchen Systemen hängt auch mit ihrer engen Beziehung zu den Vanadiumphosphoroxid(VPO)-Katalysatoren zusammen, die in der heterogenen Katalyse sehr selektive Oxidations-und Bindungsaktivierungsprozesse ermöglichen.…”
Section: Professor Giulia De Petris Gewidmetunclassified